Automated model generation and sizing of aircraft structures. Issue 2 (7th March 2016) - Führer, Tanja; Willberg, Christian; Freund, Sebastian; Heinecke, Falk
Abstract : Purpose: To obtain a good start configuration in the early design phase, simulation tools are used to create a large number of product designs and to evaluate their performance. To reduce the effort for the model generation, analysis and evaluation, a design environment for thin-walled lightweight structures (DELiS) with the focus on structural mechanics of aircrafts has been developed. Design/methodology/approach: The core of DELiS is a parametric model generator, which creates models of thin-walled lightweight structures for the aircraft preliminary design process. It is based on the common parametric aircraft configuration schema (CPACS), which is an abstract aircraft namespace. DELiS facilitates interfaces to several commercial and non-commercial finite element solvers and sizing tools. Findings: The key principles and the advantages of the DELiS process are illustrated. Also, a convergence study of the finite element model of the wing and the fuselage and the result on the mass after the sizing process are shown. Due to the high flexibility of model generation with different levels of detail and the interface to the exchange database CPACS, DELiS is well suited to study the structural behaviour of different aircraft configurations in a multi-disciplinary design process. Originality/value: The abstract definition of the object-oriented model allows several dimensions of variability, such as different fidelity levels, for the resulting structural model. Wings and fuselages can be interpreted as finite beam models, to calculate the global dynamic behaviour of a structure, or as finite shell models.